2018
DOI: 10.4172/2155-6121.1000271
|View full text |Cite
|
Sign up to set email alerts
|

Young People’s Views on the Design of Adrenaline Auto-Injectors: A Qualitative Study

Abstract: Background: "Young people's compliance with carriage of adrenaline auto-injectors (AAI) may be as low as 41%, yet we lack research exploring their preferences regarding these devices." Objective: This qualitative study explored young people's ideas about AAI design and features which may facilitate their carriage and use. Methods: Young people aged 13-18 years prescribed an AAI for severe allergic reaction were invited to participate in in-depth, semi-structured, face-to-face interviews about AAI design. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Leach L et al, demonstrated that EpiPen delivered through intramuscular injection into the lateral thigh, is the therapy of choice for anaphylaxis (20) . Our findings, in contrast to those of another research by Sheikh A et al, indicate that this is common knowledge among private practice dentists.…”
Section: Discussionmentioning
confidence: 99%
“…Leach L et al, demonstrated that EpiPen delivered through intramuscular injection into the lateral thigh, is the therapy of choice for anaphylaxis (20) . Our findings, in contrast to those of another research by Sheikh A et al, indicate that this is common knowledge among private practice dentists.…”
Section: Discussionmentioning
confidence: 99%
“…Carrying their AAI despite its perceived inconvenience could be attributed to increased perceived severity of FA. Leach, Smith, Brown, Davies and Jones 36 suggest that adolescents aged 13–18 years were conscious about safety, speed of administration, accessibility and carriage, comprehensive instructions, indication of correct administration, visibility and precise drug delivery. AAI size and needle concern were also important, a re‐evaluation of design to make the AAI smaller may increase likelihood of carriage 10 .…”
Section: Discussionmentioning
confidence: 99%